Complex binary algebra - Yu, Xin (2015)
Complex binary algebra can be defined as a type of algebra that use packed binary representation form to implement any quaternary algebra function. Complex binary algebra is quite closely related to Boolean algebra and can be used to convert any binary function into quaternary function without any significant modification. In this reports, the complex binary algebra method had been used to express some quaternary function mathematically. Finally, some physical electronic logic circuits have been constructed to approve that the complex binary algebra method can be proper implementation. Since a quaternary digit can contain as much information as a pair of binary digits, this complex binary algebra may be quite useful in the fields of digital electronic, communication and computing.